2016
DOI: 10.1017/s1355617715001344
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Executive Functions in Patients with Chronic Acquired Brain Injury with Goal Management Training, External Cuing, and Emotional Regulation: A Randomized Controlled Trial

Abstract: Methods: Seventy patients with a verified ABI and executive dysfunction were randomly allocated to GMT (n = 33) or a psycho-educative active control condition, Brain Health Workshop (BHW) (n = 37). In addition, all participants received external cueing by text messages. Neuropsychological tests and self-reported questionnaires of executive functioning were administered pre-intervention, immediately after intervention, and at 6 months followup. Assessors were blinded to group allocation.Results: Questionnaire m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 83 publications
(155 reference statements)
5
74
0
1
Order By: Relevance
“…On the contrary, GMT seems to be more effective when it is combined with attentional and problem-solving strategies (Cantor et al, 2014;Chen et al, 2011;Miotto, Evans, Souza de Lucia, & Scaff, 2009;Novakovic-Agopian et al, 2011;Spikman et al, 2010;van Hooren et al, 2007). Recent studies, combining GMT with errorless learning techniques (Bertens, Kessels, Fiorenzato, Boelen, & Fasotti, 2015) or external cueing (Tornås et al, 2016) have confirmed this.…”
Section: Introductionmentioning
confidence: 94%
“…On the contrary, GMT seems to be more effective when it is combined with attentional and problem-solving strategies (Cantor et al, 2014;Chen et al, 2011;Miotto, Evans, Souza de Lucia, & Scaff, 2009;Novakovic-Agopian et al, 2011;Spikman et al, 2010;van Hooren et al, 2007). Recent studies, combining GMT with errorless learning techniques (Bertens, Kessels, Fiorenzato, Boelen, & Fasotti, 2015) or external cueing (Tornås et al, 2016) have confirmed this.…”
Section: Introductionmentioning
confidence: 94%
“…The relatively brief two-session goal management training adopted here (in comparison with the 14 or more hours of face-to-face GMT training typically reported 16 ) might be considered insufficient for many with ABI. Future evaluation of clinical effectiveness, should consider a more extended and tailored period of strategy and self-regulation training 16,17,22 and inclusion in the intervention of additional components that enhance likelihood of transfer of strategies 16,22,[41][42][43] .…”
Section: Generalizabilitymentioning
confidence: 99%
“…A recent trial 22 found GMT incorporating text message reminders resulted in gains on self-report and neuropsychological measures, although the independent contribution of cueing was not evaluated. Previous trials have used questionnaires or neuropsychological tests rather than real-world behavioural measures to evaluate outcome.…”
Section: Introductionmentioning
confidence: 99%
“…This training was proven to be efficient in the maintenance and realisation of intention in patients with mild to moderate cognitive deficits, especially when it was associated with other intervention strategies, Running head: EXTERNAL DEVICE AND GOAL-DIRECTED BEHAVIOUR such as external cueing, or when the GMT was implemented in daily life activities and not only in a laboratory task (Krasny-Pacini, Chevignard, & Evans, 2014). For example, Tornås et al (2016) showed that GMT associated with a daily text message that read "STOP" (the first stage of GMT), indicating to the participant that he had to interrupt his ongoing action to direct his attention towards a relevant goal, was effective in improving goal attainment in daily living activities in 33 patients who had chronic brain injury without severe cognitive impairment. Other studies showed the efficiency of an external device in the realisation of GDB, such as NeuroPage, a paging system that sends reminders according to prearranged schedules.…”
Section: Introductionmentioning
confidence: 99%